Balance and Posture in Low Back Pain Patients - N Ershad; S Kahrizi (Vesnu Publications, 2008)
Abstract Epidemiological studies showed that low back pain is one of the most important disorders in musculo-skeletal system. This disorder is common in industrial countries. Low back pain is the common care of human dysfunction and economical problems.Balance is necessary for performing activities in daily living (ADL), and it should be considered in patients with low back pain. Physiological components of afferent and efferent fibers that control balance, muscle stiffness, strength and endurance are often impaired in such patients. Peripheral components of balance include: 1) The somatosensory system which is the most important component and includes repositioning sense, kinesthesia, joint position sense and duration of muscle contraction. 2) The visual system and 3) The vestibular system. According to this literature review balance, repositioning, kinesthesia and postural control which  were impaired in chronic low back pain patients might be due to change in transmitted information by mechanoreceptors, paraspinal muscle spindle dysfunction, muscle strength and coordination, delay in muscle recruitment or increased active muscle tension. Changes of proprioception are the most important factor of impaired balance in low back pain patients. Key words: Chronic low back pain, balance, posture.